2020
DOI: 10.1029/2020wr027097
|View full text |Cite
|
Sign up to set email alerts
|

NAC2H: The North American Climate Change and Hydroclimatology Data Set

Abstract: A data set containing hydrometeorological and hydroclimatological data for 3,540 watersheds in North America is described. The data set contains four main parts: (a) observed hydrometeorological data including daily streamflow observations, precipitation, minimum temperature, and maximum temperature; (b) 20 bias‐corrected climate model projections for two Representative Concentration Pathway (RCP) scenarios and five bias correction methods; (c) hydrological model calibration parameters and simulated streamflow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…
Anthropogenic warming due to increasing greenhouse gas emission has altered the terrestrial energy budget and water cycle (Arsenault et al, 2020;Erler et al, 2019). These changes have aggravated the uneven redistribution of water resources and resulted in more severe weather-related disasters (Broderick et al, 2019;Do et al, 2020).
…”
mentioning
confidence: 99%
“…
Anthropogenic warming due to increasing greenhouse gas emission has altered the terrestrial energy budget and water cycle (Arsenault et al, 2020;Erler et al, 2019). These changes have aggravated the uneven redistribution of water resources and resulted in more severe weather-related disasters (Broderick et al, 2019;Do et al, 2020).
…”
mentioning
confidence: 99%
“…In particular, GHGESs, downscaling and bias correction were not included in the analysis. In comparison, the North American Climate Change and Hydroclimatology Dataset (NAC 2 H) database (Arsenault et al, 2020) offers 16 000 combinations, allowing the examination of future streamflow uncertainty. In this regard, the relative variance contribution of the climate dataset is best examined in comparison to that of GCMs, the most studied source of climate change impact uncertainty.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 10 CMIP5 GCMs from 10 different modeling centers were selected for this study, as shown in Table 1. They were selected as a subset of the GCMs used to set up the North American Climate Change and Hydroclimatology (NAC 2 H) database (Arsenault et al, 2020). The number of GCMs (10) was selected as a compromise between having an accurate representation of GCM climate sensitivity variability and keeping the large computational burden of this project reasonable.…”
Section: General Circulation Models (Gcms)mentioning
confidence: 99%
See 1 more Smart Citation
“…The observed daily streamflow data used in this study were obtained from three sources, i.e. the Global Runoff Data Centre (GRDC; http://www.bafg.de/GRDC/, Lehner 2012), the Canadian model parameter experiment (CANOPEX) database (Arsenault et al 2016(Arsenault et al , 2020, and some catchments of China (Gu et al 2018). The GRDC dataset comprises river discharge data for more than 9,500 stations from 161 countries.…”
Section: Observed Streamflow Datamentioning
confidence: 99%